Ontology of the School Leadership Journey - Masoumi, Maryam; Khalkhali, Ali; Doostar, Mohammad; Pali, Samira (Assessment and Practice in Educational Sciences, 2026)
This study was conducted with the aim of uncovering the ontology of the school leadership journey as an existential and internal phenomenon. The research conceptualizes leadership as a “mode of being within the school lifeworld.” Using a qualitative approach and an interpretive phenomenological design, data were collected through in-depth interviews with 27 school principals in the city of Rasht. Data organization was performed through a three-stage coding process (open, axial, and selective). These organized data were then analyzed using interpretive phenomenology. The findings indicate that the school leadership journey is a nonlinear, complex, and existential process that emerges within the context of “liminal situations”—moments of crisis, ambiguity, and internal transformation. In this journey, the school leader gradually moves from the “inauthentic self”—a self shaped by organizational and social expectations—toward the “authentic self” through suspending certainties, intersecting roles, and redefining one’s situatedness. This process occurs not in isolation but through deep interactions with teachers, students, and parents, and through confronting the structural challenges of the school environment. Furthermore, the findings show that school leadership is not a “task” but a way of “being”—an existential condition in which the leader, through a perceptive and empathetic presence, creates meaning from within lived experiences. By redefining school leadership as an existential journey, this article opens the way for rethinking leadership preparation programs and educational policymaking, emphasizing the necessity of cultivating the “leader’s being” rather than merely teaching “managerial skills.”